Efforts to Cultivate Patience in Early Childhood through the August 17th Competitions - Hidayati, Novi; Ramadhanti, Silvani; Suvina, Suvina; Silvia, Vivi (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
This research is motivated by the importance of cultivating patient behavior from an early age because this patient behavior is useful for the future. The purpose of this study was to see the development of patient behavior in the August 17th competition activities. This study uses a Literature Review using three stages, namely data collection, data assessment, and drawing conclusions. The results of this study are August 17th competition activities that can be carried out on children aged 4-5 years, namely the flag relay race, putting balls in a basket, cracker eating competition, marble carrying competition in a spoon, filling water into bottles, dribbling balloons. Although these activities are competitions that can build a healthy competitive spirit, these activities can also increase children's sense of pleasure, and can improve several aspects of child development, namely, cognitive, language, motoric, and social emotional, especially patient behavior, such as training children to be patient waiting for their turn to play then children will learn calmly and not rush in taking, dribbling, or putting in objects. In addition, children learn not to get angry and not give up or accept when they do not win.